Outage probability of two‐way hybrid satellite‐terrestrial relaying networks with hardware impairments - Jingjing Shi; Tong Mu; Xiaofeng Tao (The Journal of Engineering, 2023)
Abstract The system outage probability of two‐way hybrid satellite‐terrestrial relaying networks with hardware impairments is investigated, using a novel method which features appropriate signal‐to‐noise‐and‐distortion ratio expression adjustment. A concise closed‐form lower bound expression is derived, which is in good agreement with the exact outage probability in all signal‐to‐noise ratio regions. Based on the tight bound, an asymptotic expression is obtained, revealing that the hardware impairments coin the system outage probability ceiling. The deducing method, characterized by generality, can be applicable to various realistic fading channels. Simulation results validate the derived expressions.